Pendampingan Pembayaran Pajak Bumi dan Bangunan yang Berstatus Sewa pada Warga Rt 10 Rw 05 Kelurahan Bareng Kecamatan Klojen Malang - Pudji Lestari; Hardi Susilo; Novy Karmelita I; Dewi Retnowati (jurnal ABDIMAS Indonesia, 2024)
Taxes are levied based on legal norms to cover the costs of producing collective goods and services to achieve general welfare and to increase the development of a country. One source of tax funds comes from Land and Building Tax. Refusal to pay, evasion, or resistance to taxes is generally a violation of the law. Taxes are one source of government funds for development, both central government and regional government. If a person has fulfilled the subjective and objective requirements, then he is obliged to pay tax. However, the problem often faced by the government is the lack of taxpayer awareness of their obligation to pay taxes. In this community service, the Indocakti Malang College of Economics team carried out assistance activities regarding reducing land and building tax payments for residents of RT 10 RW 05 whose land and buildings are still leased.